Influence of electrolitic solution of silver on functional fctivity of rabbit neutrophils - I. V. Chimaeva; S. B. Avakimjan; I. S. Sever; A. N. Kostylev; A. B. Vanjants; S. V. Chigrin (Кубанский научный медицинский вестник)
To evaluate the activity of microbicidal system of neutrophylic granulocytes while stimulated by different doses of electrolytic solution of silver (ESS) to increase the absorbing and digesting potential of microbic bodies in phogocytosis. In the research there were used 44 male rabbits of equal weight. After obtaining check index of phagocytosis the investigated doses of ESS were given intravenously with saccharose. In 30, 60 and 120 minutes blood samples were taken to investigate the core parameters of phagocytic activity of neutrophyles (activity of microbicidal system of neutrophylic granulocytes, absorbing and digesting potential of microbic bodies). As a consequence of introvenous input of ESS the number of active neutrophyles increased, as well as the amount of bacterias absorbed and digested. The most effective dose was 0,025 mg of silver per kg. Small amounts of ESS efficiently stimulate the microbicidal system of neutrophylic granulocytes, which is shown by the increase of phagocytic activity.